Analysis of the Influence of Work Discipline, Motivation and Leadership Style on Performance of Automobile Authorized Dealer Company - Ferdy Leuhery; Ratnawita; Andi Amang; Mulyadi; M. Wahab Khasbulloh (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The goal of this study was to assess the impact of leadership style, work motivation, and work discipline on employee performance in one of automobile dealer company. This study employs quantitative research methodologies, as well as data gathering strategies such as questionnaire distribution and library data. Non-probability sampling with saturation sampling approach was applied on 90 workers. Multiple linear regression analysis was utilized to analyze the data using the SPSS. The findings revealed that the variable of leadership style had a substantial impact on employee performance. Employee performance is significantly influenced by work motivation. Employee performance is significantly influenced by work discipline. Employee performance is influenced by leadership style, job motivation, and work discipline all at the same time. The percentage indicates that the factors of leadership style, work motivation, and work discipline can explain more than 90% of the employee performance variable. Other variables not investigated in this study account for 7% of the variance.